EVALUATING THE ROLE OF THE COMMITTEE IN IMPROVING THE QUALITY OF EDUCATION - Umiyati UMIYATI (Journal of Education and Leadership in Education, 2021)
This study aims to evaluate how the role of the school committee in improving the quality of education at SDN Peninggilan 5. The method used in this research is a qualitative method, with a descriptive approach and a Provus model (inequality by comparing the standards set by the Decree of the Minister of National Education Number 044 / U / 2002 and its implementation in SDN Peninggilan 5. The results showed that the role of the school committee as a provider of consideration, supporter, controller and liaison had been implemented but was maximally determined by the government. As a giver of consideration, the committee has not been seen to be active in providing input and consideration in planning school programs and policies. As a supporter, the School Committee has been active in providing support for the procurement and management of infrastructure, human resources, and funding, in carrying out its role as a controller of the planning and implementation of school programs, reports of observations are still in the form of oral and incidental information. The role as a liaison is good enough, but the cooperative relationship with the community is still lacking. In general, the Peninggilan 5 State Elementary School (SDN) committee plays a role in improving the quality of the school by helping morally and materially.